2022
DOI: 10.1101/2022.07.01.498405
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Context-dependent transcriptional remodeling of TADs during differentiation

Abstract: Metazoan chromosomes are organized into discrete domains (TADs), believed to contribute to the regulation of transcriptional programs. Despite extensive correlation between TAD organization and gene activity, a direct mechanistic link is unclear, with perturbation studies often showing little effect. To follow TAD dynamics during development, we used Capture Hi-C to interrogate the TADs around key differentially expressed genes during mouse thymocyte maturation, uncovering specific remodeling events. Notably, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 78 publications
6
7
0
Order By: Relevance
“…Figure 1B shows a significant positive correlation (Spearman’s ρ = 0.56, t-test p -value <1e-200) between IC and IR scores, indicating that increased transcriptional activity is associated with enhanced intra-gene condensation. This result is consistent with prior research on mouse ESC 29 , Drosophila 30 and mouse DP and DN3 thymocytes 31 . We also checked that such a correlation remains mainly independent of the phosphorylation status (Ser5P and Ser2P) of Pol II ( Fig.S2 ), which is associated with different dynamical and interacting states of the polymerase 57 .…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Figure 1B shows a significant positive correlation (Spearman’s ρ = 0.56, t-test p -value <1e-200) between IC and IR scores, indicating that increased transcriptional activity is associated with enhanced intra-gene condensation. This result is consistent with prior research on mouse ESC 29 , Drosophila 30 and mouse DP and DN3 thymocytes 31 . We also checked that such a correlation remains mainly independent of the phosphorylation status (Ser5P and Ser2P) of Pol II ( Fig.S2 ), which is associated with different dynamical and interacting states of the polymerase 57 .…”
Section: Resultssupporting
confidence: 93%
“…In this study, we analyzed publicly-available Micro-C data of mESC 13,29 to investigate the relationship between transcriptional activity and chromosome organization. Our findings align notably with previous studies 2931 . Specifically, we showed that, on average, at the single-gene level (2kbp-1Mbp), intra-gene contact enrichment, structural patterns (gene-loops, promoter-stripes, Fig.3E) and the degree of insulation from the surrounding genomic regions correlate positively with Pol II occupancy along the gene (Fig.1 ,2 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Since Kit is inactive and an insulation is absent in MEFs, we presume transcription to provide the insulation. It is in agreement with the study revealing that transcription modulates chromosome folding during mouse thymocyte maturation with single activated genes forming an insulated region within TADs 35 . Models of cohesin loading and transcription at different states suggested RNA polymerase II (RNAP) to act as a barrier to loop extrusion 36 .…”
Section: Discussionsupporting
confidence: 92%